Verb And Predicate Coordination In Ibibio - Duncan, Philip; MAJOR, TRAVIS; Udoinyang, Mfon (My University, 2019)
This paper reports on the ‘and’-word nyʌ́ŋ in Ibibio verbal coordination. Like English and, Ibibio possesses morphologically invariant coordinators linking NPs, PPs, and CPs. However, these cannot coordinate verbs and predicates, unlike and in English. Many African languages distinguish between nominal and verbal coordinators (Welmers 1973: 305), but Ibibio showcases this distinction in a unique way. Subject agreement and inflection for tense and negation suggest that nyʌ́ŋ is a verb, resembling “‘and’-verbs” in Walman (Brown & Dryer 2008). Closer inspection reveals that nyʌ́ŋ patterns more like an adverb or functional head, expanding our understanding of what constitutes ‘and’ cross-linguistically.
Keywords: Ibibio; predicate coordination; verb